Encapsulation of phenolic extract of pollen in chitosan coated liposomes and in-vitro bioaccesibility studies - Kadı Hızır, İlayda (Institute of Science And Technology, 2019)
Bee products have been in traditional medicine for a long time. The raw materials, crude extracts and purified active compounds have been found to exhibit interesting bioactivities, such as antimicrobial, anti-inflammatory and antioxidant activities. Honey are the main bee products used by humans. In addıtıon to honey, commercial bee products also include propolis, bees wax, royal jelly and pollen. Each of these bee products are, or are becoming, economically significant. Moreover they are known to have several potent bioactivities. For example, bee pollen is reported to improve energy, to supports the immune system, to help maintain good health. Bee pollen is collected by the honey bee. Pollen are composed about 50% polysaccharide, 1–20% fats and lipids, 6–28% protein, 6% amino acids, 4–10% simple sugars and accompanied by a variety of secondary plant products such as terpenes, carotenoids, flavonoids. Bee pollen has been known as a strong supplement with its bioactive ingredients since ancient times. The intake of pollen extracts has been suggested to provide health benefis and phenolics found in pollen have considerable value on human diet so they associated with decreasing the risks of chronic diseases. Polyphenolic compounds are produced by plants and represent a different group of phytochemicals, including well-known subgroups of phenolic acids, natural dyes, lignans, flavonoids etc. These natural bioactive compounds have a variety of beneficial effects including anticarcinogenic, antioxidant activities. Moreover, they are protection against coronary diseases as well as antimicrobial activities. However, phenolics are not stable and sensitive to disruption through factors such as pH, temperatures (higher than 60-80°C), presence of light, presence of ascorbic acid, enzymes. Mixing of phenolics with solubilized proteins may cause precipitation and aggregation form solution. In addition, phenolics may polymerize thereby losing their solubility and activity. To protect phenolic compounds, different encapsulation methods can be employed. Encapsulation can also allow masking of odour and colour of bioactive compound. There are several encapsulation methods such as fluid bed coating, emulsification, extrusion and cyclodextrin encapsulation, coacervation, liposome encapsulation. Nano-liposomal encapsulation method is applicable due to its easily feasible, hydrophilic and lipophilic properties. They are used as carrier systems for both oil soluble and water functional compounds such as antimicrobials, flavors, antioxidants, and bioactive compounds. Therefore, they have imporant potential uses for food, pharmaceutical, and agriculture industri. Liposomes are structural systems with a structurally negative charge. Typical sources of polar lipids are egg or soy lecithin. However, simple liposomes are fragile particles. One of the big problem is aggregation of liposomes because they tend to attach to each other. Consequently, particle size distribution can be changed. The other big limitation is their tendency to leak of covered material over time. Therefore, it has been shown that it is necessary to cover the structure with a second layer an oppositely charged biopolymer such as proteins and carbohydrates to maintain their structure. Covering liposomes with another layer of biopolymer may improve their kinetic stability and hence make the use of such systems industrially feasible. Moreover, to increase their mechanic and kinetic stability as well as to make the use of such delivery systems. This study is purposed to encapsulate phenolics extract of pollen in chitosan coated liposomes and enhance their in vitro bioaccesibility. In this studying, concentrations of 0.1% and 0.2% were studied to investigate the optimum encapsulation efficiency in primary liposomes. There was a reverse relation between pollen extract concentration and encapsulation efficiency. Whether the highest encapsulation efficiency was found to be 81 % at 0.1 (w/v) concentration of pollen extract, 0.2% (w/v) concentration of pollen extarcts with 71%. To make the spectrophotometric measurments easier due to multiple dilution in the next steps, 0.2 % concentration of encapsulation efficiency was selected. The particle size of the primary liposomes at a concentration of 0.2 % w/v was measured as 96.28 nm and ζ– potencial was measured as -31 mV. Negatively charged liposomes were covered by electrostatic deposition of positively charged chitosan layer. Layer-by-layer deposition method was used for coavered the primary anionic liposomes with cationic chitosan (0.4 w/v%). Change of encapsulation efficiency (EE%) of bioactive compounds in primary and chitosan coated (secondary) was determined, the secondary liposomes had the higher EE%. The particle size of the secondary liposomes (chitosan covered) at a concentration of 0.2 % w/v was measured as 395 nm and ζ– potential was measured as 54 mV. TPC was determined to be 17.13 ± 1.32 mg GAE/L on the surface and 446.20 ± 0.87 mg GAE/L was found interior of liposome. TFC on the surface was found 135.6 ± 3.6 mg RE/L and 514.8 ± 23.6 mg RE/L interior of liposome. According to the DPPH assay, TAC was measured as 27.46 ± 4.85 mg TEAC/L on the surface and 505.5 ± 24.6 mg TEAC/L interior of liposome while TAC was measured 21.04 ± 5.8 mg TEAC/L on the surface, 504.7 ± 19 mg TEAC/L interior of liposome in terms of CUPRAC assay. The protection of pollen extract phenolics by liposomal systems during in vitro digestion was determined by comparing freeze dried pollen extract, primary liposome with pollen extract and secondary liposome with pollen extract. It is showed that covering the liposomes with chitosan layer provided the liposome stability and to enhanced their bioaccessibility. Regarding total antioxidant capacity, total phenolic content and total flavonoid content, liposomal systems showed the better protection level of phenolics both before and after in vitro digestion. TPC and TFC, the bioaccesibility of pollen phenolics were increased approximately 4 and 2 folds, respectively. According to CUPRAC and DPPH results, antioxidant capacity enhanced approximately 2 and 3 times, respectively. Results that determined after application of in vitro digestion method, in which mouth, gastric media and intestines were simulated, were close to each other and it can be said that encapsulation with liposome and chitosan as secondary layer maintained bioactive compounds and then capsules released that compounds in intestines where they would be available for body absorbtion. Regarding the effect of in vitro digestion on phenolics, maximum phenolic compound degradation was observed in freeze dried pollen extract. The results showed that approximately 70% of phenolic compounds of freeze dried pollen extract was degraded after in vitro digestion. The phenolic compounds were detected in higher amounts in secondary liposome dispersions rather than in primary liposome dispersions after in vitro digestion, which might be explained by the interaction between phenolic compounds and chitosan. The phenolic acids profile and their bioaccesibility of pollen extract and pollen extract in nano-liposomal systems was determined by high performance liquid cyhrotomography (HPLC). There were detected 6 phenolic compounds. Their stabilty in gastro-intestinal digestion showed differences which based on molecular structure of phenolics and their location in the liposome. The interaction of these compounds with oil bases molecules and carbohydrate was an important parameter of their bioaccesibilty and degration level. Moreover, the content and location of them in liposome structure (interior or surface) is another factor to determine the protection degree. In conclusion, this study showed that liposomes are good carriers for polyphenols. They may be coated with a chitosan biopolymer to increase their kinetic stability. Liposomal encapsulation increased the total antioxidant capacity, total phenolic and total flavonoid content. Liposomal encapsulation enhanced in vitro bioaccesibility of phenolics. It is a promising way to develop functional foods and food supplements.In literature, there are some studies about encapsulation of phenolic extracts. To our knowledge, it is the first study to encapsulate phenolics in pollen extract in chitosan coated liposomes.

Geleneksel tıpta arı ürünleri uzun süreden beri çeşitli amaçlar için kullanılmaktadır. Arı ürünlerinin, ham ekstart olarak ve saflaştırılmış aktif bileşiklerinin, antimikrobiyal, antienflamatuar ve antioksidan aktiviteler gibi önemli biyoaktiviteler gösterdiği görülmüştür. Arı ürünleri arasında bal, insanlar tarafından kullanılan en çok kullanılan temel arı ürünüdür. Balın yanı sıra, propolis, balmumu, arı sütü ve polen de son zamanlarda fonksiyonel gıda olarak kullanılmaya başlanmıştır. Bu arı ürünlerinin her biri ekonomik olarak önem kazanmakta ve zamanla kullanim alanları artmaktadır. Üstelik, her birinin farklı potansiyel biyoaktiviteye sahip olduğu araştırmalarda görülmüştür. Örneğin, arı poleninin bağışıklık sistemini desteklediği, enerjiyi artırdığı ve sağlığa yaralı olduğu çeşitli çalışmalarda kanıtlanmıştır. Arı poleni, bal arısı tarafından toplanır ve polenler yaklaşık %50 polisakarit, %1-20 yağ ve lipitler, %6-28 protein, %6 aminoasitler, % 4-10 basit şekerlerden oluşur ve bunun yanısıra terpen, karotenoidler, flavonoidler gibi çeşitli ikincil bitki ürünlerini de içermektedirler. Polen çok eski tarihlerden beri içinde bulundurduğu biyoaktif bileşenler ile güçlü bir besin takviyesi olarak bilinmektedir. Özellikle polen içerisinde bulunan fenolikler, antioksidan aktivitesi güçlü, fakat biyoyararlılıkları düşük biyoaktif bileşenlerdir. Polen içerisinde bulunan polifenoliklerin insan beslenmesinde önemli görevleri vardır, aynı zamanda kronik hastalık risklerini azaltma ile doğrudan ilişkilidirler. Polifenolik bileşikler genel olarak bitkiler tarafından üretilir ve en iyi bilinen fenolik asit alt grupları, doğal boyalar, liganlar, flavonoidler vb. dahil olmak üzere geniş bir fitokimyasal grubu temsil eder. Bu doğal biyoaktif bileşikler, antikanserojen, antioksidan aktiviteler dahil olmak üzere çok çeşitli faydalı etkilere sahiptir. Ayrıca, antimikrobiyal aktivitelerin yanı sıra koroner hastalıklara karşı da koruma sağlarlar. Fakat, fenolikler, pH, sıcaklıklar (60-80°C'den yüksek), ışık varlığı, askorbik asidin varlığı, enzimler gibi faktörlerden dolayı bozulmalara karşı hassas ve stabil değildir. Bunun yanısıra fenoliklerin çözündürülmüş proteinlerle karıştırılması, çökmelere neden olabilir. Ek olarak, fenolikler polimerleşebilir ve sonucunda çözünürlük ve etkinliklerini kaybedilir. Fenolik bileşikleri korumak için farklı enkapsülasyon yöntemleri kullanılabilir. Enkapsülasyon teknikleri, fenolik bileşikleri korurken aynı zamanda istenmeyen kokunun maskelenmesine ve biyoaktif bileşiğin renginin korunmasına da yardımcı olur. Akışkan yataklı kaplama, emülsifikasyon, ekstrüzyon siklodekstrin enkapsülasyon, koaservasyon, ve lipozom ile enkapsülasyon gibi çeşitli enkapsülasyon yöntemleri vardır. Lipozomlar yapısal olarak negatif yüklü yapısal sistemlerdir. Tipik lipozom kaynakları, yumurta veya soya lesitindir. Bununla birlikte, basit lipozomlar kırılgan parçacıklardır. Ve en büyük problemlerden biri, lipozomların kümelenmesidir, çünkü lipozomlar yapısal olarak birbirlerine bağlanma eğilimindedir. Bunun sonucu olarak, partikül büyüklüğü dağılımı değişebilir. Diğer problemlerden birisi ise zaman içinde kaplanmış malzemenin sızıntısı olma eğilimidir. Bu nedenle, lipozom yapısını, korumak için proteinler veya karbonhidratlar gibi zıt yüklü bir biyopolimerin yapısının ikinci bir katmanla kaplamanın gerekli olduğu görülmüştür. Lipozomların başka bir biyopolimer tabakası ile kaplanması kinetik stabilitelerini geliştirebilir ve bu nedenle bu tür sistemlerin kullanımını endüstriyel olarak uygulanabilir hale getirebilir. Mekanik ve kinetik kararlılıklarını arttırmanın yanı sıra bu tür dağıtım sistemlerini de kullanılabilir hale getirir. Bu çalışmada, fenoliklerce zengin polen ekstratlarınının kitosan kaplı lipozomlar ile enkapsüle edilmesi ve in vitro biyoyararlılıklarının arttırılması amaçlanmıştır. Enkapsülasyon uygulaması ile bu biyoaktif bileşenlerin olumsuz çevre koşullarına dayanıklılığı artırılırken, biyoyararlılığının da arttığı görülmüştür. Polen yapısı, görünümü ve tadı nedeni ile ham olarak çocuklar tarafından sevilerek tüketilmediği için ekstratı elde edilerek besin takviyesi haline getirilmesinin ön çalışması hedeflenmektedir. Polen ekstratları, % 0.2 ağırlık/hacim konsantrasyonunda enkapsüle edilerek analizler yapılmıştır ve spektrofotometrik yöntemler kullanılarak toplam fenolik madde miktarı, toplam antioksidan kapasitesi belirlenmiştir. Folin-Ciocalteu yöntemi ile toplam fenolik madde miktarı, DPPH ve CUPRAC yöntemi ile toplam antioksidan miktarı tayin edilmiştir. Bu çalışmada lipozomlar iki farklı konsantrasyonda (%0.1 ve %0.2) enkapsüle edilmiştir. %0.1 ağırlık/hacim konsantrasyonunda enkapsülasyon verimi %81, %0.2 ağırlık/hacim konsantrasyonunda enkapsülasyon verimi %71 olarak ölçülmüştür. Spektrofotometrik analizlerin daha kolay yapılabilmesi için polen ekstartı fenolikleri %0.2 konsantrasyonunda enkapsüle edilmiştir. Bu konsantrasyonunda partikül büyüklüğü ve zeta potansiyeli ölçülmüştür. Yapısal olarak lipofilik karakterde bulunan polenin enkapsülasyonunda kitosanla kaplı ikincil lipozomlar kullanılmıştır. Bu yöntem ile hazırlanan birincil lipozomların partikül büyüklüğü 96.28 nm ve ζ –potensiyali -31 mV olarak ölçülmüştür. Negatif yüklü lipozomlar, pozitif yüklü kitosan ile kaplanmış ve primer anyonik lipozomları katyonik kitosanla (% 0,4 ağırlık/hacim ) kaplamak için tabaka tabaka biriktirme yöntemi kullanılmıştır. Primer ve kitosan kaplı (sekonder) lipozomların enkapsülasyon verimi belirlenmiş ve sekonder lipozomların enkasülasyon veriminin daha yüksek olduğu görülmüştür. Sekonder lipozomların (kitosan kaplı) % 0.2 ağırlık/hacim konsantrasyonunda partikül büyüklüğü 395 nm ve zeta potansiyel potansiyeli 54 mV olarak ölçülmüştür. Spektrofotometrik analiz sonuçları incelendiğinde ise toplam fenolik madde miktarı lipozom yüzeyinde 17.13 ± 1.32 mg GAE/L ve lipozom içerisinde 446.20 ± 0.87 mg GAE/L olarak bulunmuştur. Toplam flavonoid madde miktarı lipozom yüzeyinde 135.6 ± 3.6 mg RE/L ve lipozom içerisinde 514.8 ± 23.6 mg RE/L olarak bulunmuştur. DPPH yöntemine göre toplam antioksidan miktarı lipozom yüzeyinde 27.46 ± 4.85 mg TEAC/L ve lipozom içerinde 505.5 ± 24.6 mg TEAC/L olarak bulunmuştur. CUPRAC yöntemine göre toplam antioksidan miktarı lipozom yüzeyinde 21.04 ± 5.8 mg TEAC/L mg/L ve lipozom içerinde 504.7 ± 19 mg TEAC/L olarak bulunmuştur. Yüksek performanslı sıvı kromotografisi kullanılarak enkapsüle edilmemiş (dondurularak kurutulmuş) ve enkapsüle edilmiş (kitosan ile kaplı olan ikincil lipozomlar ) polen ekstraktının biyoyararlılıkları ve in vitro sindirim öncesi ve sonrası fenolik asit profilleri araştırılmış sonuç olarak 6 temel fenolik bileşen tespit edilmiştir bu bileşenler flavon-3-ol monomerleri, flavan (kuersetin) ve fenolik asitlerden meydana gelmektedir. Tespit edilen fenolik bileşenlerin mide-bağırsak sistemindeki in vitro sindirimi fenolik bileşenlerin molekül yapısına ve lipozomda bulundukarı yere ve lipozomdaki miktarlarına göre farklılıklar göstermektedir. Bunların yanı sıra fenolik bileşenlerin yağ molekülleri ve karbonhidrat ile etkileşimi de bu bileşenlerin biyoyararlılıklarını ve degradasyon seviyelerini etkileyen bir diğer önemli parametredir. Ağız, gastrik ortam ve bağırsakların simüle edildiği in vitro sindirim yönteminin uygulanmasından sonra belirlenen sonuçlar birbirine yakın olarak bulunmuştur. Sekonder tabaka olan kitosan kaplı lipozomlarda biyoaktif bileşiklerin daha iyi korunduğu görülmüştür. In vitro sindirimin fenolikler üzerindeki etkisine ilişkin olarak, dondurularak kurutulmuş polen ekstartlarının en fazla fenolik bileşik bozulmasına sahip olduğu gözlenmiştir. Dondurularak kurutulmuş polen ekstraktının fenolik bileşiklerinin yaklaşık olarak % 70'inin in vitro sindirimden sonra bozunduğunu saptanmıştır. Fenolik bileşik miktarı, fenolik bileşikler ve kitosan arasındaki etkileşimle açıklanabilecek in vitro sindirimden sonra birincil lipozom dispersiyonlarından ziyade ikincil lipozom dispersiyonlarında daha yüksek miktarlarda tespit edilmiştir. Sonuc olarak, yaptığımız çalışma göstermiştir ki; lipozomlar polifenoller için iyi taşıyıcılardir ve kinetik stabilitelerini arttırmak için bir kitosan biyopolimeri ile kaplanabilirler. Lipofilik bileşenlerin organik solvent kullanılmadan enkapsülasyonu mümkündür ve lipozom ile enkapsülasyon, biyoaktif bileşenlerin daha iyi korunmasını sağlayarak biyoyararlılıklarını arttırmıştır. Lipozomal enkapsulasyonu, toplam antioksidan kapasitesi, toplam fenolik ve toplam flavonoid içeriğini artırmıştır. Lipozom enkapsulasyonu ile fenoliklerin in vitro biyoyararlılıkları da artmıştır. Lipozom ile enkapsulasyonun, fonksiyonel gıda ve gıda takviyeleri geliştirmek için umut verici bir yol olduğu söylenebilir. Literatürde kakao kabuğu atığı ekstartının içerdiği aktif bileşenlerin nano-lipozomal sistemler ile enkapsüle edilmesi ile ilgili mevcut çalışmalar bulunmaktadır. Lipofilik karakterizasyona sahip polen ekstartlarının enkapsüle edilerek yapılarının korunduğu, fenolik maddeler, antioksidanlar gibi güçlü biyoaktif bileşenlerin dayanımının arttığı görülmüştür.
Fenoliklerce zengin polen ekstartlarının kitosan kaplı lipozomlar ile enkapsulasyonu ve biyoyararlılık calismalari
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2019
Tez (Yüksek Lisans)-- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Pollen, Lipids, Bioaccesibility; Çiçek tozu, Lipidler, Biyoyararlılık